Feasibility of sludge ozonation for stabilization and conditioning - Park, KY; Ahn, KH; Maeng, SK; Hwang, JH; Kwon, JH (TAYLOR & FRANCIS INC, 2003)
A pilot-scale sludge treatment plant was built to investigate the feasibility of ozonation processes for waste activated sludge treatment. Ozonation of wastewater sludge resulted in mass reduction by mineralization as well as by supernatant and filtrate recycle. Another advantage of sludge ozonation is a significant improvement of settleability and dewaterability. Experimental results showed that mass reduction of 70 % and volume reduction of 85 % compared with the control sludge was achieved through the sludge ozonation at a dose of 0.5 gO(3)/gDS. It is also interesting to note that the filterability deteriorates up to ozone dose of 0.2 gO(3)/gDS and then improves considerably at a higher ozone dose. The filterability could be improved by chemical conditioning even at a low ozone dose. The economic feasibility by cost analysis reveals that ozonation processes can be more economical than other alternative processes for sludge treatment and disposal at small-sized wastewater treatment plants.
Keywords: ACTIVATED-SLUDGE; BOUND WATER; OZONE